Manufaktur dan Uji Kinerja Mesin Perajang Hijauan Multifungsi - mawardi, indra; bahri, Samsul; Cebro, Irwin Syahri; Hamdani, Hamdani (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2023)
The need for forage and tuber feed for farmers is increasing daily. The existence of chopping machines that have been developed before still needs to improve in the work process, where the work process has only one focus, namely chopping. Apart from that, machines that have been previously produced have a fixed construction (not mobile), thus limiting machine mobilization. The research aims to create innovations in the form of multifunctional forage chopping machines. This machine combines the processes of chopping and crushing greens and tubers. Apart from that, this machine is designed to use wheels, making it easier to move. The research method is divided into design and manufacturing processes, followed by performance testing. Performance testing uses elephant grass and cassava as raw materials using 1600, 1800 and 2000 rpm engine speeds. From manufacturing results, multifunctional forage chopping machines are available. This machine has 750 x 450 x 700 mm dimensions with a capacity for chopping elephant grass ranging from 72-150 kg/hour and crushing cassava ranging from 85-279 kg/hour. An engine speed of 2000 rpm shows the highest chopping and crushing results.